EXCEL Spreadsheet to Simulate Leachate Transport in Groundwater from Landfills for Subdistrict Administration Organization / เอ็กซ์เซลสเปรดชีทจำลองการเคลื่อนที่ของน้ำชะขยะในน้าบาดาลออกจากหลุมฝังกลบสำหรับองค์การบริหารส่วนตำบล - กิจการ พรหมมา, Kitchakarn Promma / (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 1 (2556): January - June 2013, 2014)
องค์การบริหารส่วนตาบลจัดการขยะมูลฝอยของตนเอง หลุมฝังกลบอาจเกิดการรั่วซึมของน้าชะขยะลงไปปนเปื้อนน้าบาดาลสะอาด ถ้ามีโปรแกรมจาลองแบบการแพร่กระจายตัวของน้าชะขยะในน้าบาดาลฟรี ใช้งานง่าย และได้ผลดี อย่างน้อยสามารถคานวณความยาวของการแพร่กระจายของน้าชะขยะได้ถูกต้อง จักช่วยให้ชุมชนจัดการปัญหาสิ่งแวดล้อมเช่นนี้ได้อย่างเข้มแข็ง วัตถุประสงค์ของงานวิจัยนี้ คือ เพื่อสร้างโปรแกรมจาลองแบบน้าชะขยะที่แพร่กระจายออกจากแหล่งกาเนิดไปในน้าบาดาล โดยแปลงคาตอบโดเมนนิโกให้คานวณความเข้มข้นของตัวชี้วัดมลพิษได้ในเอ็กซ์เซลสเปรดชีท ตัวชี้วัดที่ใช้ คือ คลอไรด์ วิธีทาเริ่มต้นด้วยการนาพจน์ต่างๆ ในคาตอบโดเมนนิโกไปใช้เป็นสดมภ์ของเอ็กซ์เซลสเปรดชีท เมื่อคูณกลับค่าของพจน์ต่างๆ จะได้ความเข้มข้นสัมพัทธ์เปรียบเทียบกับความเข้มข้นของคลอไรด์ที่แหล่งกาเนิด โปรแกรมวาดกราฟเส้นโดยอัตโนมัติระหว่างความเข้มข้นของคลอไรด์ที่ลดลงทีละน้อยออกจากแหล่งกาเนิดไปตามแนวแกน x จากนั้นโปรแกรมถูกนาไปสาธิตการใช้งานจริงที่หลุมฝังกลบ ตาบลบึงกอก อาเภอบางระกา จังหวัดพิษณุโลก การจาลองแบบทาเพียงซีกขวาข้างเดียว และให้ซีกซ้ายเป็นภาพสะท้อน ผลการสาธิตใช้งานแสดงว่า พลูมที่ได้จากการจาลองแบบใกล้เคียงกับค่าจริง แต่อาจมีปัญหาเรื่องข้อจากัดของข้อมูลนอกสถานที่ฝังกลบขยะ รวมถึงความรู้ของบุคลากรในองค์การบริหารส่วนตาบล ที่จาเป็นต้องอธิบายเกี่ยวกับตัวแปร กราฟ คาลิเบรชัน และความน่าเชื่อถือ สรุปว่า วิธีการสร้างโปรแกรมทาง่าย ใช้งานง่ายและฟรี และมีความถูกต้องในการคานวณความยาวแกนพลูมน้าชะขยะ คำสำคัญ: น้าชะขยะ เอ็กซ์เซลสเปรดชีท แบบจาลองมลพิษ น้าบาดาล องค์การบริหารส่วนตาบล Subdistrict Administration Organization manages their own solid wastes. Leachate from the wastes can penetrate through landfill liners into clean groundwater. If a contaminant transport model is available for free to simulate the leachate plume, simple to use, and accurate at least for estimating the leachate plume axis, the model can strengthen the community to handle this environmental problem. The objective of this study was to build a program that can simulate  leachate migrated from a source in groundwater by transforming the Domenico solution to be able to calculate concentrations of index contaminants in an EXCEL spreadsheet. The index used in this study was chloride. The study began with assigning terms in the Domenico solution into columns in the spreadsheet. Multiplying terms resulted in chloride concentrations in groundwater in a specific space and time. The program drew automatically a line graph of declining chloride concentrations along the x axis. After that, the program demonstration used data from a landfill in Buengkok, Bang-rakam, Phitsanulok. The simulation was made only on the right side of the plume axis whereas the left side was a reflection. Results show a good match between simulated and field values. However, weakness of the application includes a lack of data outside the property line and weak background knowledge of personels working at the Subdistrict Administration Organization which need explanation on parametering, graph, calibration, and reliability. In conclusion, the program was simple to make and use, available for free, and accurate in estimating the leachate plume length. Keywords: Leachate, EXCEL Spreadsheet, Contaminant Transport Model, Groundwater, Subdistrict Administration Organization
Keywords: น้ำชะขยะ เอ็กซ์เซลสเปรดชีท แบบจำลองมลพิษ น้ำบาดาล องค์การบริหารส่วนตำบล Leachate, EXCEL Spreadsheet, Contaminant Transport Model, Groundwater, Subdistrict Administration Organization